DIALEKTIKA EKSISTENSIAL DALAM KISAH MUSA-KHIDIR - Istnan Hidayatullah (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2020)
This research focuses on the existential dialectical momentum contained in the story of Moses and Kheer. Judging from the title has confirmed that the approach used is the philosophy of existentialism, which in this case was introduced by Martin Heidegger. The results of this study, among others, reveal the relationship between the characters in the story (Musa and Kheer), hereinafter referred to as Dasein with other entities, such as objects that are tools, objects not tools and other Dasein. In addition, he also managed to explore the three existential phases experienced by each Dasein, namely the existential phase, the facticity phase, and the destruction phase. Musa and Khidir in Surah al-Kahf: 65-82 experienced these three phases, from the time they met, the adventure to the separation.